Geographic Experiments in Empirical Research - Otto, Karl-Heinz; Mönter, Leif O.; Hof, Sandra; Wirth, Joachim (Journal of Geography Education, 2010)
Geography teaching introduces the specific thought and work methods of geography and other earth sciences into school. Experimenting as the decisive way of gaining scientific knowledge plays a key role when dealing with physiogeographically relevant topics. The requirements as regards content and methods imposed on students experimenting in geography lessons are varied and demanding. However, no competence-oriented empirical studies on geographic experiments have been published so far. It is the aim of this contribution to summarize the national and international state of research concerning the empirical teaching and learning research on experimenting. It is thereby intended to discuss empirically verified theory models that exist against the background of the technical characteristics of the geographic experiment with regard to their suitability for a research project in the field of geography education.